Transformações do imaginário arquitetônico: do antecedente ao consequente - Lanna Larissa Rodrigues Rêgo de Oliveira (2022)
This research investigates the students' architectural imaginary transformations in different moments of their formative process in Architecture and Urbanism, from the following questions: How do Architecture students transform themselves in terms of their architectural imaginaries at different times of formation? What are the possible links between these transformations and the didactic practices adopted in the teaching of architectural design? Starting from the central hypothesis that the architectural imaginary can provide evidence about the nature of didactic practices adopted in project teaching, we developed an exploratory investigation in order to interpret what we call Antecedent Imaginary (representations of spatialization and imagetic representations of future students and students of the 1st period in the graduation in Architecture and Urbanism) and Consequent Imaginary (representations of spatialization and imagetic representations of graduates in Architecture and Urbanism). Therefore, interviews were conducted with students from two different moments of graduation from the same educational institution, as well as future students (students already approved in the entrance exam and who had not yet started taking classes). The main objective was to generate information that goes back to the transformation of the architectural imaginary, inscribed in these three moments of the academic course. The approach chosen for data processing is qualitative, carried out through the thematic analysis method. The data collected reveal 4 structuring themes for the analysis of the Antecedent and Consequent Imaginaries, in addition to 34 categories that report to the representations that emerge about the built the act of designing and the vectors of influence related to architecture, which authorizes the identification of trends among the imaginaries, their transformations and their possible correlations with practices proper to formal architectural education. The responses to the transformations were obtained through the identification of spatial, subjective, projective and professional interference from the formal environment and non-formal vectors on the student imaginary. The analysis shows that, among advanced students, despite a natural expansion of the imaginary, this is not necessarily more diverse in relation to the patterns of spatialization, images and architectural references. In addition, among the newcomers, an early convergence of discourse is identified, where there is a tendency to the reproduction of certain values and teaching postures incorporated even before the contact with the project disciplines, which suggests an urgent need for diversification of references in the teaching environment of Architecture and, consequently, the didactic practices that incite them.